Experimental psychology meets behavioral ecology: what laboratory studies of learning polymorphisms mean for learning under natural conditions, and vice versa. (2nd January 2020) - Smith, Brian H.; Cook, Chelsea N.
Abstract: Behavior genetics, and specifically the study of learning and memory, has benefitted immensely from the development of powerful forward- and reverse-genetic methods for investigating the relationships between genes and behavior. Application of these methods in controlled laboratory settings has led to insights into gene–behavior relationships. In this perspective article, we argue that the field is now poised to make significant inroads into understanding the adaptive value of heritable variation in behavior in natural populations. Studies of natural variation with several species, in particular, are now in a position to complement laboratory studies of mechanisms, and sometimes this work can lead to counterintuitive insights into the mechanism of gene action on behavior. We make this case using a recent example from work with the honey bee, Apis mellifera .